IMPLEMENTASI KONSEP PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) KECAMATAN DI KOTA PEMATANGSIANTAR - Saut Parlindungan Sinaga; Marlon Sihombing; Agus Suriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
This study used a qualitative approach with descriptive form that menyajikat picture of good governance phenomena that occur at the level of districts in the province of North Sumatra. This research was conducted in 2016, located in Pematangsiantar specifically phenomenon observation area of ​​research carried out in several districts scattered in Pematangsiantar.Results of research descriptively explained that the application of the values ​​of good governance in the sub-districts scattered in Pematangsiantar is good enough. Nevertheless strategic efforts aimed at improving the implementation of the spirit of the values ​​of good governance will be developed as sustainable as needed empowerment and service to the community.There are several factors that significantly affect the successful implementation of the values ​​of good governance throughout the District Government in Pematangsiantar which includes aspects of delegation of authority fully to implementing the wheels of government as to regions remote / rural areas, improvement of infrastructure especially in districts away from the district capital, and no less importantly include improved aspects of community development districts through qualified human resources and be able to compete as in trying to meet their basic needs.